Normative scores for the three factor eating questionnaire (TFEQ-R18) in a UK population-based cohort - Cara F. Ruggiero; Laura Kudlek; Julia Mueller; Simon J. Griffin; Stephen J. Sharp; Nick J. Wareham; Soren Brage; Nita G. Forouhi; Ken K. Ong; Amy Ahern (Appetite, 2026)

Spatiotemporal patterns in Diadema antillarum settlement in the Florida Keys: implications for habitat restoration - Julia S. Skowronski; William C. Sharp; Lindsay J. Spiers; Colette J. Feehan (Coral Reefs, 2025)
The long-spined sea urchin ( Diadema antillarum ) is a key herbivore on Caribbean coral reefs, but mass mortality events have severely reduced its populations, diminishing grazing pressure and contributing to reef degradation. In the Florida Keys, where D. antillarum remains scarce, the extent and variability of larval settlement are poorly understood, yet this information is critical for predicting and managing population recovery. To address this, we quantified monthly settlement rates using standardized Astroturf plates deployed across a gradient of reef habitats at nine reef sites from 2017 to 2023. We found that settlement was significantly higher at offshore bank-barrier reefs than inshore patch reefs, with greater settlement observed in the middle/upper Florida Keys compared to the lower Keys. Seasonal variation indicated peak settlement in summer, suggesting that larval supply may be influenced by seasonal oceanographic processes. Despite evidence of settlement, recruitment success remains uncertain, as post-settlement factors such as predation or environmental conditions may limit survival. These findings provide key insights for D. antillarum restoration efforts, highlighting offshore reefs in the middle/upper Florida Keys as priority sites for enhancing settlement and improving post-settlement habitat to support population recovery. Future studies should investigate the biophysical mechanisms driving the spatial and temporal settlement patterns identified here, to develop a predictive framework for settlement events that can further inform population management.

Hypertonic Saline Nasal Rinse Intervention: Immunomodulatory Effects in Dairy Workers - Grant Erlandson; Sheryl Magzamen; Julia L. Sharp; James Seidel; Jill A. Poole; Mary Bradford; Joshua W. Schaeffer (Journal of Agromedicine, 2025)

The impact of behavioural weight management interventions on eating behaviour traits in adults with overweight or obesity: a systematic review and meta-analysis - Laura Kudlek; Patricia Eustacio Colombo; Amy Ahern; Struan Tait; Natasha Reid; Milindu Wickramarachchi; Aiswarya Lakshmi; Stephen J. Sharp; Marie Spreckley; Julia Mueller; Rebecca A. Jones (Appetite, 2024)

Feasibility and acceptability of an acceptance-based guided self-help programme for weight loss maintenance - Julia Mueller; Rebecca A. Jones; Rebecca Richards; Jennifer Woolston; Fiona Whittle; Andrew J. Hill; Carly A. Hughes; Robbie Duschinsky; Stephen J. Sharp; Clare Boothby; Jennifer Bostock; Penny Breeze; et al. (Appetite, 2023)

JA:2021-31. Does the Use of a Nasal Lavage Intervention Improve Pulmonary Function for Dairy Workers? - James Seidel; Grant Erlandson; Julia D. Labadie; Sheryl Magzamen; Julia Sharp; Ken Jones; Matthew Nonnenmann; Stephen J. Reynolds; Joshua W. Schaeffer (Journal of Agromedicine, 2020)

JA:2021-6. Effectiveness of a Low-cost Intervention: Changes to Cytokines and Microbiome among Bioaerosol Exposed Dairy Workers - Grant Erlandson; Sheryl Magzamen; Julia Sharp; Ken Jones; Matthew Nonnenmann; Stephen J. Reynolds; Joshua W. Schaeffer (Journal of Agromedicine, 2020)

Localized Impacts of Hurricane Irma on Diadema antillarum and Coral Reef Community Structure - Julia N. Kobelt; William C. Sharp; Travis N. Miles; Colette J. Feehan (Estuaries and Coasts, 2020)

Peptide Inhibitor of Complement C1 (PIC1) Inhibits Growth of Pathogenic Bacteria - Pamela S. Hair; Magdielis Gregory Rivera; Adrianne I. Enos; Susan E. Pearsall; Julia A. Sharp; Nazita Yousefieh; Frank A. Lattanzio; Neel K. Krishna; Kenji M. Cunnion (International Journal of Peptide Research and Therapeutics, 2019)

Characterization and Separation of Cancer Cells with a Wicking Fiber Device - Suzanne M. Tabbaa; Julia L. Sharp; Karen J. L. Burg (Annals of Biomedical Engineering, 2017)

Spatio-temporal analysis of flowering using LiDAR topography - Samantha Hart; Elena Mikhailova; Christopher Post; Patrick McMillan; Julia Sharp; William Bridges (Journal of Geographical Sciences, 2017)

Clinical and genomic evaluation of 201 patients with Phelan–McDermid syndrome - Sara M. Sarasua; Luigi Boccuto; Julia L. Sharp; Alka Dwivedi; Chin-Fu Chen; Jonathan D. Rollins; R. Curtis Rogers; Katy Phelan; Barbara R. DuPont (Human Genetics, 2014)

An Integrated WebGIS Framework for Volunteered Geographic Information and Social Media in Soil and Water Conservation - Joshua D. Werts; Elena A. Mikhailova; Christopher J. Post; Julia L. Sharp (Environmental Management, 2012)